Arrhythmic Mitral Valve Prolapse: A Comprehensive Review - Yuyan Deng; Jinfeng Liu; Shan Wu; Xiaoming Li; Huimei Yu; Lili Tang; Meng Xie; Chun Zhang (Diagnostics, 2023)
Mitral valve prolapse (MVP) is a prevalent cardiac disorder that impacts approximately 2% to 3% of the overall population. While most patients experience a benign clinical course, there is evidence suggesting that a subgroup of MVP patients face an increased risk of sudden cardiac death (SCD). Although a conclusive causal link between MVP and SCD remains to be firmly established, various factors have been associated with arrhythmic mitral valve prolapse (AMVP). This study aims to provide a comprehensive review encompassing the historical background, epidemiology, pathology, clinical manifestations, electrocardiogram (ECG) findings, and treatment of AMVP patients. A key focus is on utilizing multimodal imaging techniques to accurately diagnose AMVP and to highlight the role of mitral annular disjunction (MAD) in AMVP.